Indigenous Knowledge: Revitalizing Everlasting Relationships between Alaska Natives and Sled Dogs to Promote Holistic Wellbeing - Janessa Newman; Inna Rivkin; Cathy Brooks; Kathy Turco; Joseph Bifelt; Laura Ekada; Jacques Philip (International Journal of Environmental Research and Public Health, 2022)
Introduction: Indigenous peoples have documented their culture’s history in oral stories, revealing lessons about holistic relationships fostering perseverance. Despite vast differences in time, relationships and stories are equally important today. Athabascans retain their values, life skills, and wellness through cultural practices. Creating opportunities for youths to learn through reciprocal relationships increases wellness in Indigenous communities, highlighting the significance of community-developed programs that connect youths to their place and culture. Method: Athabascan youths in rural Alaska get hands-on experience and Elder mentorship working with sled dogs in the Frank Attla Youth and Sled Dog Care-Mushing Program (FAYSDP). Through a community-based participatory research partnership with the community of Huslia and Jimmy Huntington School, we examined how FAYSDP affects youths, and how relationships within culture and land promote wellbeing. Fifteen middle and high-school youths shared their perspectives on how FAYSDP impacts them and their community using photovoice and digital storytelling. Nineteen adults contributed their perspectives in focus groups. We used emerging themes (inductive) and Athabascan cultural values and elements of social capital (deductive approaches) to analyze the qualitative data. Results: Findings illustrate how FAYSDP promotes wellbeing by empowering youths to apply what they learn to generate their own knowledge, while centering communities around culturally significant practices such as dog mushing. It connects youths to their home and their cultural values, using dogs as the driving force to bridge generations and foster youth wellness. Discussion: We discuss implications for community-based programs that engage Elders as teachers and the land as their classroom to promote youth holistic wellness.